Locomoter behavior of the Galapagos giant tortoise Geochelone elephantopus: (abstract) - Walker, Warren F. (1978)
BIB Now: 7160
Inglés
Keywords: Galapagos giant tortoise; Tortugas terrestres gigantes; Locomotor; Behavior; Comportamiento